FORMATION OF FUTURE TEACHERS’ VALUE ATTITUDE TO THE TEACHING PROFESSION: PROBLEMS AND PROSPECTS - Nevmerzhytska, Olena; Pahuta, Myroslav; Chubinska, Nataliya; Hevko, Oksana; Hamerska, Iryna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
Pedagogical education determines the quality of professional training of specialists in all spheres of functioning of society and the state, which therefore contributes to their stability and development. In this regard, serious requirements are put forward to the personality of a modern teacher. However, the training of a teacher with an innovative type of thinking, ready for self-improvement throughout life, faces a number of problems: organizational, content, financial, etc. The development of modern pedagogical education is greatly influenced by informatization and the development of an open society, the development of civil society, the need to form a new cultural type of personality, etc. High requirements for the training of future teachers in modern conditions are in conflict with the falling prestige of this profession. In modern Ukrainian society the pedagogical profession is usually highly appreciated at the scientific and theoretical level, as well as at the declarative state level. However, despite this, in practice this assessment in terms of salary and working conditions is low. After all, the assessment of teachers by themselves as well as parents is not very high. The survey of future teachers (n=102) also confirmed this tendency. This circumstance actualizes the search for ways to form future teachers' value attitude to the teaching profession. Value attitude is the subject's internal acceptance of an object as a value. The value attitude to the pedagogical profession is represented by the unity of three components: cognitive, emotional and functional. In order to form in the mind of future teachers a value attitude to the teaching profession in the educational process of a higher education institution, a system was created in which the emphasis was placed on the formation of motivation for professional activity, modeling and solving professional and pedagogical tasks, as well as the permanent involvement of students in practical activities. The implemented pedagogical experiment proved the effectiveness of such a system.